Traffic performance analysis of unsignalized intersection using the Traffic Conflict Parameter technique - Muhammad Isradi; Zainal Arifin; Muhammad Ikhsan Setiawan; Ronny Durrotun Nasihien; Joewono Prasetijo (Universitas Mercu Buana, 2022)
The unsignaled intersection of Jalan H Djole – Jalan Pasar Lama in Bekasi City is a densely populated commercial area with high economic activity. The lack of facilities and infrastructure that causes traffic jams at the intersection also raises the potential for conflict. This study aims to analyze the level of service, the type of conflict, and the traffic conflict complexity at an unsignaled intersection. The field survey method obtains primary data on the conflict approach and traffic volume. The analysis showed that the highest traffic volume was 3,810 passenger cars unit/hour with a DS value of 1.06 and LOS F. The number of conflicts that occurred during one hour of observation at peak hours was 420. Most of the conflicts that arose were straight-right, turned movements of 138.